Microstructural Controls on Mixed Mode Dynamic Fracture Propagation in Crystalline and Porous Granular Rocks. Issue 3 (10th March 2022) - Braunagel, Michael J.; Griffith, W. Ashley
Abstract: Brittle fracture propagation in rocks is a complex process due to significant grain‐scale heterogeneity and evolving stress states under dynamic loading conditions. In this work, we use digital image correlation and linear elastic fracture mechanics to make instantaneous measurements of the opening (mode I) and in plane shear (mode II) components of the stress intensity field during dynamic mixed mode crack initiation and propagation in crystalline and granular rocks. Both rock types display some similar fracture behaviors as observed in engineered materials, including rate dependent fracture initiation toughness and a direct relationship between propagation toughness and crack velocity; however, measured propagation toughness is higher than quasi‐static values at crack velocities well below the branching velocity in both rocks. Additionally, due to grain scale controls on the fracture process, mixed mode crack propagation is fundamentally different between these two rock types. Mixed mode propagation is energetically more favorable than pure opening mode propagation in sandstone, while the opposite is true in granite. Furthermore, following initiation, propagation in granite occurs so as to minimize the mode II contribution, irrespective of the initiation conditions, while fractures in sandstone maintain a non‐negligible mode II contribution during propagation across the sample. Plain Language Summary: Fracture initiation and growth in rocks is a complex process due to grain scale heterogeneity in the material and changing stress states. However, many models for rock failure are based on experimental observations made in continuum‐like engineered materials. In this study, we use digital image correlation and linear elastic fracture mechanics to better understand the effects of grain scale heterogeneity and loading conditions on the dynamic fracture process in granite and sandstone. Our results are generally consistent with experimental observations in engineered materials, including increasing fracture toughness with loading rate and crack velocity in both rock types. However, grain scale controls result in large discrepancies in the energy required for crack growth under mixed mode opening and shear loading conditions in sandstone and greater propagation toughness than predicted by models in both rocks. Key Points: Digital image correlation and linear elastic fracture mechanics allow instantaneous measurement of stress intensity during crack growth Mixed mode fracture propagation is energetically favorable in granular rocks compared with pure mode I Dynamic propagation toughness in both rock types is higher than quasi static values in both rock types